Recommendations for the diagnosis and practical management of paediatric eosinophilic oesophagitis - Carolina Gutiérrez Junquera; Sonia Fernández Fernández; Gloria Domínguez-Ortega; Víctor Vila Miravet; Roger García Puig; Ruth García Romero; Ana Fernández de Valderrama; Rebeca Andradas Rivas; Carmen Alonso Vicente; Marina Álvarez Beltrán; Josefa Barrio Torres; Patricia Barros García; et al. (Elsevier, 2020)
Eosinophilic oesophagitis is an emerging and chronic disorder mediated by the immune system, and is characterised by symptoms of oesophageal dysfunction and inflammation with isolated eosinophil infiltration in the oesophagus. It is more common in males and in atopic subjects, and the symptoms vary with age. In younger children, there is vomiting, abdominal pain and dietary problems, with dysphagia and food impaction in older children and adolescents. The diagnosis is based on the presence of symptoms and oesophageal inflammation with ≥15 eosinophils/high power field, and after ruling out other causes of oesophageal eosinophilia. Without treatment, the disease usually persists and can progress to fibrostenotic forms more common in adults. The treatment options included proton pump inhibitors, empirical elimination diets, and swallowed topical corticosteroids. Maintenance therapy is advisable after the induction treatment. Diet is the only treatment that is directed at the cause of the disease, on identifying the triggering food or foods. The response to the treatments requires a histological assessment due to the poor agreement between the symptoms and the oesophageal inflammation.The practical management of Eosinophilic oesophagitis presents with challenges, due to, among other causes, the current lack of availability of specific drugs, and its approach with, occasionally complex, diet treatments. The present document, prepared by the Working Group on Eosinophilic Gastrointestinal Disorders of the Spanish Society of Paediatric Gastroenterology, Hepatology and Nutrition, has as its objective to help in the diagnostic and therapeutic approach to paediatric eosinophilic oesophagitis, based on the recent evidence-based consensus guidelines. Resumen: La esofagitis eosinofílica es una enfermedad emergente, crónica, mediada por el sistema inmune y caracterizada por síntomas de disfunción esofágica e inflamación con infiltración eosinofílica aislada en el esófago. Es más frecuente en varones y en sujetos atópicos y los síntomas varían con la edad: en niños pequeños se manifiesta con vómitos, dolor abdominal y problemas con la alimentación y en niños mayores y adolescentes con disfagia e impactación alimentaria. El diagnóstico se basa en la presencia de síntomas e inflamación esofágica con ≥ 15 eosinófilos/campo de gran aumento, tras descartar otras causas de eosinofilia esofágica. Sin tratamiento, la enfermedad suele persistir y puede evolucionar a formas fibroestenóticas más frecuentes en el adulto. Las opciones terapéuticas incluyen inhibidores de la bomba de protones, dieta de eliminación empírica y corticoides deglutidos. Tras el tratamiento de inducción es aconsejable la terapia de mantenimiento. La dieta es el único tratamiento que se dirige a la causa de la enfermedad, al identificar los alimentos desencadenantes. La respuesta a los tratamientos requiere la evaluación histológica, por la escasa concordancia entre los síntomas y la inflamación esofágica.El manejo práctico de la esofagitis eosinofílica presenta desafíos debido, entre otras causas, a la falta de disponibilidad actual de fármacos específicos y a su abordaje con tratamientos dietéticos, en ocasiones, complejos. El presente documento, elaborado por el Grupo de Trabajo de Trastornos Gastrointestinales Eosinofílicos de la Sociedad Española de Gastroenterología, Hepatología y Nutrición Pediátricas, tiene como objetivo facilitar el abordaje diagnóstico y terapéutico de la esofagitis eosinofílica pediátrica, con base en las recientes guías de consenso basadas en la evidencia.